The negacism and the deconstruction of racism in brazilian society (Research, Society and Development, 2022)
The article proposes a reflection on a possible process of deconstruction of racism in Brazilian society. Starting from the need to recognize racism in the country, since its denial as a structural element of oppression in society has been an argument purposely raised to delegitimize those who propose to foster this debate. To achieve the objectives, a qualitative approach is used, using the exploratory research method, through the bibliographic technique, based on specific theoretical studies on the subject. Historical landmarks will be analyzed to understand that there is a link between racism and slavery and that it does not end with abolition. Events around the world are capable of revealing the undeniable existence of racism and its serious consequences today. We will also problematize what we could call “new faces of racism” given the increasing frequency of subtle racism and a decrease in the most explicit form, which leads society to imagine that we are overcoming racism, when in reality it has taken over. other ways. This transformation leads us to an analysis of the path we are taking so that society rethinks its way of living with others and the possibility of promoting a change in the social structure and consequent deconstruction of the phenomenon in Brazil.